Liquid phase human papillomavirus genotype analysis of aspirated metastatic head and neck squamous cell carcinoma: Fine needle aspiration supernatant is a rich source of tumor DNA that can increase the diagnostic yield. Issue 1 (5th September 2020) - Hao, Yansheng; Mehrotra, Meenakshi; Lam, Hansen; Si, Qiusheng; Salem, Fadi; Lu, Dan; Gitman, Melissa; Miles, Brett; Posner, Marshall; Houldsworth, Jane; Westra, William H.
Abstract: Background: Most patients with human papillomavirus (HPV)‐related head and neck squamous cell carcinoma (HNSC) present with lymph node metastasis. In these patients, fine needle aspiration (FNA) is not only a diagnostic tool, but a means for determining HPV status. HPV status, in turn, is used to determine tumor origin, prognosis, and even guide therapy. Thus, the limited sampling afforded by FNA must be optimized to meet heavy clinical demands. Purpose: The purpose of this study was to determine whether the residual supernatant portion of the FNA could serve as a resource for reliable determination of HPV status Design/Method: 25 FNAs from 24 patients with metastatic HNSC underwent HPV genotyping of post‐centrifuged supernatant fluid from FNA needle rinses. HPV genotyping was performed using two real time PCR‐based assays, the two‐step LightCycler and the one‐step automated cobas HPV tests. HPV status of the supernatant was compared with the paired FNA cell blocks and/or surgical tissue samples. Results: The supernatant was adequate for HPV testing in 24 (96%) of 25 cases. Of these, 14 (56%) were HPV positive and 11 (44%) negative by the LightCycler assay. HPV16 was the most commonly detected genotype (n = 12). When results of supernatant and paired cell block testing were compared, HPV status was concordant in all cases. The LightCycler method was more sensitive than the cobas assay due to its ability to detect an expanded profile of HPV variant genotypes. Conclusion: The current standard of practice for patients with HNSC who undergo FNA is to construct a cell block and then discard the supernatant. This supernatant is a rich source of tumor DNA that can be used to detect HPV status. It should not be wasted.